Corporate Social Responsibility and Organizational Initiatives – Case of Developing Countries - Shmailan, Abdulwahab S (International Journal of Psychosocial Rehabilitation, 2020)
The present study presents a multilevel literature review about CSR in the context of the developing countries, highlighting multiple distinctive aspects of CSR. The study initially provided a theoretical framework, following an empirical analysis. The literature analyzed the CSR activities and programs in the general context of the developing countries, while later concentrating it on a specific country, Saudi Arabia. The findings have provided an overview of CSR and its potential benefits. Various CSR-related considerations were identified encompassing strengths of the consumer trust, corporate reputation, and development of the legitimacy sense with the stakeholders. The findings imply towards adopting tri-sector partnerships in CSR involving Saudi government, private sector, and society, for substantial development. However, it can be concluded that the success of CSR in the developing economies depends largely upon socio-political and historical factors, which stands-out as the primary challenge.